When Plagiarism Is A Matter - Wahyuni, Nur Cahyati (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
The high education world is retested with resurfacing the plagiarism practice of the scientific papers in the academic community. The Plagiarism joins in the realm of academic integrity, where the honesty of the scientific process and the contributions of others in a paper of an academic community should be recognized in.The software of Plagiarism detection on the paper can be used to reduce the risk of plagiarism and academic integrity. However, the information sharing and appropriate learning about the plagiarism issue itself is more important for improving the understanding which directs the behavior of anti-plagiarism.This Literature Study give a line description on raising awareness of plagiarism. Â It is not only higher educationâs responsibility, but also primary and secondary education. The Application of Information Literacy program earlier will assist in the formation of individuals who are away from plagiarism behavior.